2022
DOI: 10.1038/s41380-022-01483-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals novel ethnicity-specific rare variants associated with Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is the most common multifactorial neurodegenerative disease among elderly people. Genome-wide association studies (GWAS) have been highly successful in identifying genetic risk factors. However, GWAS investigate common variants, which tend to have small effect sizes, and rare variants with potentially larger phenotypic effects have not been sufficiently investigated. Whole-genome sequencing (WGS) enables us to detect those rare variants. Here, we performed rare-variant association stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Although our prediction model using only biomarkers identified in this study might be insufficient to early diagnosis of AD, our findings can serve as potential biomarkers for predicting disease prognosis. In previous studies, we reported that 24 miR-eQTLs (the relationship between SNPs and miRNA expression) and three clinical factors (age, sex, and APOE4 alleles) successfully classified MCI patients into low and high risk of MCI-to-AD conversion 13 . Moreover, recent survival analyses have showed that plasma phosphorylated tau (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our prediction model using only biomarkers identified in this study might be insufficient to early diagnosis of AD, our findings can serve as potential biomarkers for predicting disease prognosis. In previous studies, we reported that 24 miR-eQTLs (the relationship between SNPs and miRNA expression) and three clinical factors (age, sex, and APOE4 alleles) successfully classified MCI patients into low and high risk of MCI-to-AD conversion 13 . Moreover, recent survival analyses have showed that plasma phosphorylated tau (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of AD—that is, the presence of genetic risk factors—is estimated to be 60% to 80% 11 . A large number of genetic factors undoubtedly contribute to the etiopathogenesis and progression of AD, and some of them have been identified via whole-genome sequencing analyses 12 , 13 and genome-wide association studies 14 16 . The AD risk genes are implicated in the immune response ( CLU, CR1, CD33, EPHA1, MS4A4E/MS4A6A, ABCA7, PTK2B, TREM2 , and TREML2 ), endocytosis ( BIN1, PICALM , and CD2AP ), and lipid processing ( APOE, ABCA7 , and SORL1 ) 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 2, 2023. ; https://doi.org/10.1101/2023.03.01.530618 doi: bioRxiv preprint diseases, atypical clinical presentations, or prognostic responses [6][7][8][9]. However, the large volume of off-machine data from WGS presents new challenges in terms of analysis time and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in sequencing technology and lower sequencing costs, whole-genome sequencing is playing an increasingly important role in single-gene disease screening or diagnosis, individualized cancer therapy, and pharmacogenomic screening [1][2][3][4][5]. Because it allows for the rapid, simultaneous detection of virtually all genes in a patient that may be associated with disease, which is particularly effective for patients with very rare or novel diseases, atypical clinical presentations, or prognostic responses [6][7][8][9]. However, the large volume of off-machine data from WGS presents new challenges in terms of analysis time and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, next-generation sequencing (NGS) technology has enabled collection of large amounts of massive parallel sequence (MPS) information. NGS technology has also enabled whole-genome resequencing of species with reference genome sequences [ 24 , 25 , 26 ]. Using NGS, transgenes can be detected as deletions of introns [ 27 , 28 , 29 ], enabling screening for nontargeted transgenes by comparing the detected intron deletions to annotated gene information (i.e., the intron location in reference sequences).…”
Section: Introductionmentioning
confidence: 99%